Effects of cooperative, competitive, and individualistic goal structures on achievement: A meta-analysis - Johnson, David W.; Maruyama, Geoffrey; Johnson, Roger; Nelson, Deborah; Skon, Linda (Psychological Bulletin, 1981)
Reviewed 122 studies (listed in an appendix) and compared the relative effectiveness of cooperation, cooperation with intergroup competition, interpersonal competition, and individualistic goal structures in promoting achievement and productivity in North American samples. These studies yielded 286 findings. Three meta-analysis procedures were used: voting method, effect-size method, and z-score method. Results indicate that (a) cooperation is considerably more effective than interpersonal competition and individualistic efforts, (b) cooperation with intergroup competition is also superior to interpersonal competition and individualistic efforts, and (c) there is no significant difference between interpersonal competitive and individualistic efforts. Through multiple regression, a number of potentially mediating variables for these results are identified. (18 ref)
Keywords: 2